An improved method for paleoflood reconstruction from core sediments in the upper Yellow River - Pang, Hongli; Jia, Yunxia; Li, Fuqiang; Qin, Lin; Chen, Liying (Frontiers in Earth Science, 2023)
Fluvial deposits represent a sedimentary archive of paleohydrological information, which can be utilized to reconstruct unrecorded floods. A multi-index (grain size, end-member model, and geochemistry elements) approach of core sediments from the upper Yellow River was used to reconstruct its flood history. A high-resolution geochemical profile of the 20.71-m-deep core was obtained by an XRF core scanner. A comparison of sediment grain size with geochemical element ratios indicated that ln(Zr/Ti) can be used as a grain size proxy for the core sediment. Combined with the end-member modeling analysis, the flood energy index (FEI) was constructed to highlight the flood signals and their similar trends with sediment ln(Zr/Ti). Coarsened grain size and increased ln(Zr/Ti) suggested that a high-frequency flood phase appeared to occur in the early Holocene (11–6.5 ka) and late Holocene (3.5–0 ka), while low-frequency floods occurred in the middle Holocene (6.5–3.5 ka). An extreme hydrological phase occurred during 5.8 ka–5.9 ka, which coincided with a sharp increase in sedimentation rates from 0.14 mm/yr to 0.48 mm/yr. The flood activities at the upper reach of the Yellow River are considered to respond to climate variability with the monsoonal shift.